Clinical analysis of histiocytic necrotizing lymphadenitis in adults with fever of unknown origin: a retrospective study - Nana Xie; Wencong Zhang; Fangbing Tian; Jia Chen; Wenyuan Zhang; Qiurong Ruan; Jianxin Song (Diagnostic Pathology)
Abstract Purpose To comprehensively analyze the clinical data of histiocytic necrotizing lymphadenitis (HNL) in adults with fever of unknown origin (FUO), with the aim of enabling precise diagnosis. Patients and methods A total of 15 HNL patients with FUO were enrolled. The analysis encompassed clinical manifestations, laboratory parameters 18F-Fluorodeoxyglucose Positron Emission Tomography/Computed Tomography (18F-FDG PET/CT) imaging profiles, pathological features and therapeutic responses. Results All patients presented with fever and lymphadenopathy (predominantly cervical). Laboratory findings included leukopenia (3.28 × 10⁹/L [2.40–4.97]), elevated LDH (306 U/L [187–524]), ESR (40 mm/h [30–51]), ferritin (457.1 ng/mL [206-1823.3]), and CRP (25 mg/L [6.1–34.8]) 18F-FDG PET/CT detected metabolic lymph node abnormalities in 13 cases, primarily cervical and axillary. The pathological features were extensive coagulative necrosis of lymph nodes with reactive hyperplasia of histiocytes as well as positive or scattered positivity IHC CD3, CD4, CD8 and CD68. Corticosteroid achieved favorable responses, with only 2 cases progressing during follow-up. Conclusion In clinical practice, patients with fever and lymphadenopathy should be given due attention. Pathological examination remains the gold standard for diagnosing HNL. Glucocorticoid therapy has proven effective, and the majority of patients with HNL exhibit a favorable prognosis.